Trianon és Magyarország déli határrégiói - Lőrinczné Bencze, Edit (Közép-Európai Közlemények, 2010)
The Kingdom of Serbs, Croats and Slovenes was formed in Belgrade on 1 December 1918, however the Allied did not translate into immediate recognition of the state, because of claiming an international agreement on precisely what its border should be done. The newly formed state had border disputes with 6 countries, to the north with Hungary and Austria, to the south with Bulgaria and Albania, as well as with Italy on Adriatic territories, and with Romania on Banat. Concerning Hungary the Serbian army occupied all the territories and more reaching into the country as far as Pécs during 1918, claiming form Hungary at the Paris peace conference, which strengthened almost all of them by the treaty Trianon signed on June 4, 1920. The Serbs got Southern Hungary, Slavonia, and Croatia (confederated with Hungary for 700 years) to create the unlikely “Yugoslavia”, which, effectively, no longer exists.